Gun Ownership Trends In The United States, 1973-2000 - Ruckert, Jason Michael (2004)
In the last half century, gun ownership has been one of the most hotly debated topics in the United States. The right to bear arms was written into the U. S. Constitution and into the hearts and minds of its citizens. During the last half century, however, numerous gun control laws have been enacted at Federal, state and local levels, and it can be argued (plausibly or not) that part of the legislative intent has been to decrease the number of gun owning households in the United States. For many decades, this number hovered at one half of all households (Wright, 1995). The possible success of these gun control efforts is suggested by an apparent and rather sharp decline in the ownership percentage beginning in the 1990s. In 2000, the household gun ownership rate had decreased to 32.5% (according to the General Social Survey). The question raised in this thesis is how to account for declining gun ownership. More specifically, I ask if there has in fact been a decline in ownership, or whether the apparent decline is an illusion resulting from changing demographics. A third possibility, that social norms have changed such that admitting gun ownership in surveys is now more problematic for many people, is also considered and seems, indeed, to be the most telling line of explanation